Gene expression response under thermal stress in two Hawaiian corals is dominated by ploidy and genotype - Erin E. Chille; Timothy G. Stephens; Deeksha Misri; Emma L. Strand; Hollie M. Putnam; Debashish Bhattacharya (Ecology and Evolution, 2024)
Abstract Transcriptome data are frequently used to investigate coral bleaching; however, the factors controlling gene expression in natural populations of these species are poorly understood. We studied two corals, Montipora capitata and Pocillopora acuta, that inhabit the sheltered Kāne'ohe Bay, Hawai'i. M. capitata colonies in the bay are outbreeding diploids, whereas P. acuta is a mixture of clonal diploids and triploids. Populations were sampled from six reefs and subjected to either control (no stress), thermal stress, pH stress, or combined pH and thermal stress treatments. RNA‐seq data were generated to test two competing hypotheses: (1) gene expression is largely independent of genotype, reflecting a shared treatment‐driven response (TDE) or, (2) genotype dominates gene expression, regardless of treatment (GDE). Our results strongly support the GDE model, even under severe stress. We suggest that post‐transcriptional processes (e.g., control of translation, protein turnover) modify the signal from the transcriptome, and may underlie the observed differences in coral bleaching sensitivity via the downstream proteome and metabolome.